2023
DOI: 10.3390/ijerph20043631
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Sexes and Speed Levels in Pelvic 3D Kinematic Patterns during Running Using an Inertial Measurement Unit (IMU)

Abstract: This study aimed to assess the 3D kinematic pattern of the pelvis during running and establish differences between sexes using the IMU sensor for spatiotemporal outcomes, vertical acceleration symmetry index, and ranges of motion of the pelvis in the sagittal, coronal, and transverse planes of movement. The kinematic range in males was 5.92°–6.50°, according to tilt. The range of obliquity was between 7.84° and 9.27° and between 9.69° and 13.60°, according to pelvic rotation. In females, the results were 6.26°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…In this frame, a tendency towards external rotation of the pelvis during running was shown. External pelvic rotation during running has also been underscored by Perpina-Martinez et al (2023) in a kinematic analysis of 101 male and female adults [ 33 ]. Our study confirmed this tendency among children.…”
Section: Discussionmentioning
confidence: 99%
“…In this frame, a tendency towards external rotation of the pelvis during running was shown. External pelvic rotation during running has also been underscored by Perpina-Martinez et al (2023) in a kinematic analysis of 101 male and female adults [ 33 ]. Our study confirmed this tendency among children.…”
Section: Discussionmentioning
confidence: 99%
“…However, the similarity in the triaxial acceleration data between treadmill and ground running suggests that the results for the loading direction were unaffected [27]. Although only male subjects were included in the study, sex was standardized because sex differences have been observed in pelvic movements during running [28], which may have affected the loading pattern. Finally, although there is a correlation, other factors may also have an effect.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used inertial sensors to analyze pelvic movement in different planes and/or in different movements/contexts [38][39][40][41][42][43][44]. Some of them have been used as an evaluation method in total hip arthroplasty patients [41,42] or patients with reduced lumbar lordosis (or flat back) posture [40].…”
Section: Introductionmentioning
confidence: 99%
“…Others have analyzed their validity compared with 3D optical tracking systems during walking and sit-stand and step-up transfers [38,44] or during trunk flexion-extension movements [39]. They have also been used to investigate differences between sexes and speed levels in pelvic kinematics during running [43]. Also, studies have shown that wearable motion sensors and mobile devices have opened new possibilities in telerehabilitation, especially for balance and gait disorders.…”
Section: Introductionmentioning
confidence: 99%